Retinal structure and vessel density changes in cerebral small vessel disease - Wang, Dandan; Wang, Lina; Wang, Jinjin; Du, Yang; Wang, Kaiyue; Wang, Meizi; Yang, Liu; Zhao, Xingquan (Frontiers in Neuroscience, 2024)
Background Cerebral small vessel disease (CSVD) attaches people’s attention in recent years. In this study, we aim to explore retinal structure and vessel density changes in CSVD patients. Methods We collected information on retinal metrics assessed by optical coherence tomography (OCT) and OCT angiography and CSVD characters. Logistic and liner regression was used to analyze the relationship between retinal metrics and CSVD. Results Vessel density of superficial retinal capillary plexus (SRCP), foveal density- 300 length (FD-300), radial peripapillary capillary (RPC) and thickness of retina were significantly lower in CSVD patients, the difference only existed in the thickness of retina after adjusted relevant risk factors (OR (95% CI): 0.954 (0.912, 0.997), p = 0.037). SRCP vessel density showed a significant downward trend with the increase of CSVD scores (β: −0.087, 95%CI: −0.166, −0.008, p = 0.031). SRCP and FD-300 were significantly lower in patients with lacunar infarctions and white matter hypertensions separately [OR (95% CI): 0.857 (0.736, 0.998), p = 0.047 and OR (95% CI): 0.636 (0.434, 0.932), p = 0.020, separately]. Conclusion SRCP, FD-300 and thickness of retina were associated with the occurrence and severity of total CSVD scores and its different radiological manifestations. Exploring CSVD by observing alterations in retinal metrics has become an optional research direction in future.